1976
DOI: 10.1029/ja081i016p02805
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Injection at Synchronous Orbit and Spatial and Temporal Auroral Morphology

Abstract: Analysis of ATS 5 particle spectrograms and simultaneous meridian‐scanning photometer data (keograms) obtained at the base of the ATS field line has revealed systematic relationships between temporal and spatial auroral morphology and particle injection events. The details of these relationships depend on previous injection events, the local time of the observatory with respect to current injection events, and the extent and magnitude of current injections. A persistent zone of weak aurora is related to steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 39 publications
(37 reference statements)
2
50
1
Order By: Relevance
“…Since there are no other superposed epoch analyses using proton auroral substorms, we might try comparing our results with those of Birn et al [1997], who also used the technique of superposed epoch analysis of dispersionless injection in synchronous‐altitude particle data. Dispersionless ion injections occur simultaneously with substorm onsets [e.g., Eather et al , 1976]. Birn et al [1997] found minimal enhancement in the low‐energy ion component, but the energetic ions (above 30 keV) contributed significantly, and an average ion temperature enhancement from ∼10 to 16 keV was seen.…”
Section: Discussion Of the Superposed Epoch Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are no other superposed epoch analyses using proton auroral substorms, we might try comparing our results with those of Birn et al [1997], who also used the technique of superposed epoch analysis of dispersionless injection in synchronous‐altitude particle data. Dispersionless ion injections occur simultaneously with substorm onsets [e.g., Eather et al , 1976]. Birn et al [1997] found minimal enhancement in the low‐energy ion component, but the energetic ions (above 30 keV) contributed significantly, and an average ion temperature enhancement from ∼10 to 16 keV was seen.…”
Section: Discussion Of the Superposed Epoch Analysis Resultsmentioning
confidence: 99%
“…This was done in Figure 4 for the input data for WIC (top left) for the Gaussian fit of the same data (top right) and for the SI12 data (bottom left) and the Gaussian fit (bottom right) for a substorm which occurred on day 193, 2000, at 0958 UT. The format is identical to the auroral latitude, time, intensity plot format introduced some years ago as a Keogram [ Eather et al , 1976]. In general, the Gaussian fits on the right are extremely good representations of the original data on the left.…”
Section: Data Presentationmentioning
confidence: 99%
“…As a means to maximize the value of data from such arrays, we developed a simple data display format similar to keograms generated from auroral images (Eather et al, 1976;Samson et al, 1996) and range-time plots of radar echoes (Ponomarenko et al, 2003;Ruohoniemi et al, 1991). With the basic hardware for the experiments (i.e., fluxgate magnetometers) readily available, our understating of the waves can be improved by deploying the hardware at multiple locations and developing new techniques to analyze the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The scan takes 16 s and is carried out along the north-south geomagnetic meridian covering the whole 1801-angle range. The data are usually presented as keograms (Eather et al, 1976) showing the magnetic meridian profile in a given channel (after removal of the background) as a function of time. An archive of the data covering the last decade at Svalbard and the last two decades at Poker Flat can be found at: http://photon.gi.alaska.edu/home.html.…”
Section: Instruments and Techniquesmentioning
confidence: 99%